Numerically simulated 3D-structures of the fluctuating fields - Filippov, A.E. (Condensed Matter Physics, 2001)
Numerical simulation of a structure of the fluctuating field appearing at a kinetic
stage of the phase transition is performed for the systems with scalar
and two-component (complex) order parameters. It is found that the ordering
process is accompanied by a large-scale filamentary structure of
the fluctuating field. The dense local groups and chains of the nuclei are
created in the system. A complicated topology of the ordering is found in
the system with complex order parameter. This system creates specific
“toroidal” vortices. Kinetic scenarios in 3D-space are compared with the
2D- and 1D projections of the analogous structures previously found. Чисельне моделювання структури флуктуюючого поля виникаючого на рівні кінетичного опису фазового переходу здійснено для систем з скалярним і дво-компонентним параметрами порядку. Виявлено, що процес впорядкування супроводжується велико-масштабною
волокнистою структурою флуктуюючого поля. В системі утворюються густі локальні групи і ланцюжки ядер. Виявлено складну топологію впорядкування в системі з двокомпонентним параметром порядку. Така система утворює складні тороїдальні завихрення. Кінетичний
сценарій в 3-вимірному просторі порівнюється з попередньо одержаними дво- і одновимірними проекціями аналогічних структур.